2019
DOI: 10.1186/s13561-019-0246-6
|View full text |Cite
|
Sign up to set email alerts
|

Costing for universal health coverage: insight into essential economic data from three provinces in Cambodia

Abstract: BackgroundKnowledge of the costs of health services improves health facility management and aids in health financing for universal health coverage. Because of resource requirements that are often not present in low- and middle-income countries, costing exercises are rare and infrequent. Here we report findings from the initial phase of establishing a routine costing system for health services implemented in three provinces in Cambodia.MethodsData was collected for the 2016 financial year from 20 health centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…They also mentioned that the studies from Pakistan and Vietnam also reported similar results. Jacobs et al (2019) too highlighted that salaries and wages made up the most significant proportion of costs (44-50%), followed by medicine and materials (37-44%) in Cambodia. A similar situation was seen in India too.…”
Section: Introductionmentioning
confidence: 99%
“…They also mentioned that the studies from Pakistan and Vietnam also reported similar results. Jacobs et al (2019) too highlighted that salaries and wages made up the most significant proportion of costs (44-50%), followed by medicine and materials (37-44%) in Cambodia. A similar situation was seen in India too.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many Asian countries have invested in Health Technology Assessment to overcome some of these obstacles [31,32]. The current study complements efforts to establish a routine health services costing system in Cambodia to enable policymakers to set prices for active purchasing of health services and to aid subnational level health managers to optimize service delivery with available resources [15].…”
Section: Discussionmentioning
confidence: 89%
“…Calculating the cost of a CS using available top down costing data from Cambodia also gives different results. The costs per inpatient day from the different top down costing studies were multiplied with the ALOS of CS-patients at the public hospital and inflated to 2018 values: data of Fabricant from 2001 suggest a cost per CS of US$90.84 [35], while this would be US$100.17 using Collins' data from 2007 [36] and US$305.24 when data from 2016 by Jacobs et al [15] are used. The increased costs over time likely reflect improved services, indicating the need to base policy decisions on up-to-date data and to repeat data collection regularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study concluded that increasing health service utilization and quality could improve public health center efficiency [ 12 ]. Finally, a recent healthcare costing study found considerable differences in workload which was inversely correlated with total and unit costs within each facility level which suggests that cost-efficiency could be improved by increasing service volume [ 13 ].…”
Section: Introductionmentioning
confidence: 99%